Healthcare Needs, Experiences and Satisfaction after Terrorism: A Longitudinal Study of Survivors from the Utøya Attack - Stene, Lise E.; Wentzel-Larsen, Tore; Dyb, Grete (Frontiers in Psychology, 2016)
Background: Public health outreach programs have been developed in order to ensure that needs are met after disasters. However, little is known about survivors’ experiences with post-terror healthcare. In the present study, our objectives were to 1) describe survivors’ experiences with post-terror healthcare, 2) identify factors associated with reports of unmet healthcare needs, and 3) examine the relationship between socio-demographic characteristics, healthcare experiences and satisfaction. Methods: Our study comprised three waves of semi-structured interviews with 261/490 (53%) survivors of the Utøya mass shooting. We applied Pearson’s chi-squared tests (categorical variables) and independent t-tests (continuous variables) to compare survivors by whether or not they reported higher perceived needs than received help for psychological reactions and physical health problems, respectively. Ordinal regression analyses were applied to examine whether socio-demographic characteristics and healthcare experiences were associated with dissatisfaction. Results: Altogether 127 (49%) survivors reported very high/high help needs for psychological reactions, and 43 (17%) for attack-related physical health problems. Unmet healthcare needs were associated with higher levels of posttraumatic stress, psychological distress, somatic symptoms and less social support. Survivors with immigrant backgrounds and injured survivors who were not admitted to hospital reported unmet needs for physical health problems more often. After adjustments for socio-demographic characteristics, immigrant origin was associated with dissatisfaction with post-terror healthcare. After additionally adjusting for healthcare experiences, poor rating of the overall organization and accessibility of healthcare remained significantly associated with dissatisfaction. Conclusions: Most survivors were satisfied with the post-terror healthcare they received, yet our findings indicate that increased attention to the physical health of non-hospitalized terrorism survivors is required. Furthermore, in future outreach, particular attention should be paid to the healthcare needs of survivors with immigrant background.